2020
DOI: 10.1080/22221751.2020.1756699
|View full text |Cite
|
Sign up to set email alerts
|

Different longitudinal patterns of nucleic acid and serology testing results based on disease severity of COVID-19 patients

Abstract: Effective strategy to mitigate the ongoing pandemic of 2019 novel coronavirus (COVID-19) require a comprehensive understanding of humoral responses against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the emerging virus causing COVID-19. The dynamic profile of viral replication and shedding along with viral antigen specific antibody responses among COVID-19 patients started to be reported but there is no consensus on their patterns. Here, we conducted a serial investigation on 21 individuals i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
257
2
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(312 citation statements)
references
References 13 publications
35
257
2
12
Order By: Relevance
“…However, symptom severity may also affect the rate of seropositivity. A delayed or absent humoral response against SARS‐CoV‐2 has been reported in some patients 12 and may result in negative serology results 13 . Surprisingly, despite her immunosuppressed condition and her mild symptoms, she developed an immune response with IgM produced on day 14, which is consistent with the literature for immunocompetent patients 14 .…”
Section: Figuresupporting
confidence: 84%
“…However, symptom severity may also affect the rate of seropositivity. A delayed or absent humoral response against SARS‐CoV‐2 has been reported in some patients 12 and may result in negative serology results 13 . Surprisingly, despite her immunosuppressed condition and her mild symptoms, she developed an immune response with IgM produced on day 14, which is consistent with the literature for immunocompetent patients 14 .…”
Section: Figuresupporting
confidence: 84%
“…56 Asymptomatic patients may seroconvert later in the course of infection or may not at all. 57 Another study found that asymptomatic patients have significantly longer duration of viral shedding, lower IgG, and neutralizing serum antibody levels compared with the symptomatic group, suggesting that asymptomatic patients may mount a weaker antibody response and immunity may diminish within months of infection. 58 Although these studies demonstrate variable antibody response, IgA/IgM antibodies seem to develop during the earlier stages (indicative of recent exposure) 59 whereas IgG antibodies show up later in the course of SARS-CoV-2 infection.…”
Section: Serology Testingmentioning
confidence: 99%
“…IgG detection may improve and speed up the diagnosis of COVID-19 in symptomatic patients, particularly in negative SARS-CoV-2 PCR cases. It has been shown that in up to 15% of COVID-19-positive patients IgG antibodies are detectable during the rst week following the onset of symptoms [8], although reaching 100% of the patients required two additional weeks [8,12,13,20]. Here, we examined the performance of serology as an adjuvant for the diagnosis of COVID-19 using commercially available procedures.…”
Section: Discussionmentioning
confidence: 99%